Inducing Non-genetically Modified Induced Embryonic Sertoli Cells Derived From Embryonic Stem Cells With Recombinant Protein Factors - Xu, Chenze; Mohsin, Ali; Luo, Yanxia; Xie, Lili; Peng, Yan; Wang, Qizheng; Ahmed, Waqas; Hang, Haifeng; Zhuang, Yingping; Guo, Meijin (Frontiers in Cell and Developmental Biology, 2021)
Embryonic Sertoli cells (eSCs) possess multiple supporting functions and research value in gonadal development and sex determination. However, the limitation of acquiring quality eSCs had hindered the further application. Herein, we successfully derived non-genetically modified (non-GM) induced embryonic Sertoli-like cells (eSLCs) from mouse embryonic stem cells (ESCs) with TM4 cells derived conditioned medium containing recombinant endogenous protein factors of Sry, Sox9, Sf1, Wt1, Gata4 and Dmrt1. These eSLCs was determined through morphology, transcriptional expression level of stage-specific, epithelial and mesenchymal marker genes, flow cytometry, immunofluorescence, immunocytochemistry and functionally determined by coculture with spermatogonia stem cells. Results indicated these eSLCs performed similarly to eSCs in specific biomarkers, expression of marker genes and supporting the maturation of spermatogonia. The study induced eSLCs from mouse ESCs by defined protein factors. However, the inducing efficiency of non-GM method was still lower than lentiviral transduction method. Thus, this work established a foundation to future production of non-GM eSLCs for clinical applications and fundamental theory research.